Ulam Type Stability of a Fractional Volterra Integral Equation in the Hadamard Sense - Celiker, Fatma Ozturk; Develi, Faruk (SPRINGER BASEL AG, 2025)
This paper investigates the Ulam type stability of a fractional Volterra integral equation in the Hadamard sense. The analysis is conducted utilizing the fixed point method within a new generalized metric framework. The obtained results are derived under weaker conditions compared to similar studies and are further supported by an illustrative example.
Keywords: Hadamard fractional integral; Ulam type stability; Fixed point theorem; Mathematics